Substance use and sociodemographic correlates among adolescents in a low-income sub Saharan setting - Abio Anne; Davis Laura E; Wilson Michael L. (My University, 2022)
Background: The present study investigated the social and behavioral correlates of substance use, specifically bang or cocaine or similar drugs among a school-based sample of adolescents in a low-income urban setting
Methods: The study utilized data on 2,176 school-attending adolescents aged 11-16 years in Dar es Salaam (DES) to examine social and behavioral correlates for lifetime substance use. The correlates under investigation included, demographic - age and gender; social - poverty, parent-adolescent relationship; behavioral – truancy, aggressive behavior, injury risk; psychological - depression and suicide ideation. Bivariate and multivariate analyses were then carried out on several variables identified from the 2006 Tanzanian Global School-based Health Survey (GSHS) questionnaire.
Results: Approximately seven percent of school-attending adolescents (n=144) reported having used an illicit substance at least once during their lifetime. After adding significantly associated covariates into a logistic regression model, we found that only truancy [OR= 2.29 (CI=1.07 – 4.90)], suicide ideation [OR=4.36 (2.32 – 8.19)] and parents who had checked their adolescents' homework (OR=0.56 (CI=0.32 – 1.00)] were significantly associated with reported substance use.
Conclusions: Our results suggest that health promotion programs should simultaneously target multiple factors associated with substance use behaviors among school-attending adolescents in Dar es Salaam. They should take into account the range of psychosocial characteristics of school-attending adolescents which may be impacted by or result from substance use.